If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(9s+1)-19s=2(4s+2)-6
We move all terms to the left:
3(9s+1)-19s-(2(4s+2)-6)=0
We add all the numbers together, and all the variables
-19s+3(9s+1)-(2(4s+2)-6)=0
We multiply parentheses
-19s+27s-(2(4s+2)-6)+3=0
We calculate terms in parentheses: -(2(4s+2)-6), so:We add all the numbers together, and all the variables
2(4s+2)-6
We multiply parentheses
8s+4-6
We add all the numbers together, and all the variables
8s-2
Back to the equation:
-(8s-2)
8s-(8s-2)+3=0
We get rid of parentheses
8s-8s+2+3=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation
| x/15=3/10 | | 8(33-4y)-9y=-146 | | 13=v/26 | | 2x +5=15 | | -2/3(9x-15)=16 | | k+-283=925 | | 3.75+x=91/2 | | u/5=3/8 | | 13d=4 | | 3(x+1)-5=(5x=2) | | 3(x+1)-5=(5x-2) | | -7+7x-3x=39 | | 17=x1-5 | | 10x-1+x=3(x+5) | | -60=5(1+3n)-5 | | 3x+2(x-6)=2x-30 | | 6.8x-11.2=36.4 | | 7y+6=-8(y+3) | | 6h²-13h+5=0 | | 3.3m+2.4=18.24 | | 6=-4b+6b | | 9y+10=4(y+5) | | 3+k/14=7 | | 4x-9x-3x+6x=x | | 3k+9-7k=5 | | 8−6g=–5g | | 70=7c | | 12/36=36/n | | -3+5y=42 | | 6h-13h+5=0 | | 5(p-2.50)=3p | | 4n/8=16 |